Effect Of Blast Designs On Rock Fragmentation At Lafarge Kanthan Quarry, Chemor, Perak - Awang Kechik, Nur Aliah Hazirah (Universiti Sains Malaysia, 2018)
This study was sought to study the effects of blast design parameters on rock fragmentation. The field study was carried out at Lafarge Kanthan Quarry, Chemor, Perak for the duration of 3 weeks. After blasting, the images of muck pile were taken using suitable camera. The images then were uploaded into the WipFrag software to analyze the fragmentation generated from the blasting. The particle size distribution graphs obtained from the software had been correlated with the blast designs. The percentage cumulative passing for gyratory crusher with the feed size of 1500 mm ranges between 92.8 to 100 %. Blast design parameters such as bench height, powder factor, stemming have high correlation with the rock fragmentation. Bench height to burden ratio (H/B) shows the highest correlation to the mean fragment size with the value of R2=99.7%. Moreover, it is indicated that as the powder factor increases, the finer the mean fragment size. Powder factor also has a high correlation with the uniaxial compressive strength of the rock. The compressive strength of blasted rocks ranges between 66.01 to 115.81 MPa. The results show that the higher the uniaxial compressive strength of rock, the higher the powder factor needed. In this study, spacing to burden ratio (S/B) has a very weak correlation with the rock fragmentation. Even though there was an occurrence of oversize rocks, all blasting events had generated a good rock fragmentation with uniformity index varies from 2.09 to 2.28.